Nexus - Naam, Ramez (Naam, Ramez. Nexus (Series), 2015)
In the near future, the experimental nano-drug Nexus can link humans together, mind to mind. There are some who want to improve it. There are some who want to eradicate it. And there are others who just want to exploit it. When a young scientist is caught improving Nexus, he's thrust over his head into a world of danger and international espionage -- for there is far more at stake than anyone realizes.